The Role of Courage in the Socratic Method: Can Passions Affect Philosophical Dialogue? - Izquierdo Garcés, Josefina (2025)
This paper argues that, according to Socrates, the conditions for acquiring virtue cannot be reduced to purely cognitive elements, as passions can influence our actions. Specifically, the Laches shows that the practice of the Socratic method requires, prior to intellectual activity, mastery over one’s own character in order to achieve its goal: a harmony between what is deemed good and right action. Courage, a virtue closely tied to the control of passions, is crucial for attaining this harmony.